Deformation‐Induced Role Switching Between Ferrite and Austenite in the Precipitation of Carbides at High Temperatures in Duplex Stainless Steels. Issue 11 (17th September 2014) - Lo, Kin Ho
<x xml:space="preserve">Abstract</x> The austenite phase of duplex stainless steels is commonly considered to undergo nearly no precipitation events upon thermal annealing, whereas the ferrite phase is invariably viewed as the transforming phase. The present paper shows that the situation will be the opposite after plastic deformation and annealing at temperatures above 900 °C. The role switching in terms of carbide precipitation may be explained on grounds of the more efficient diffusion of substitutional elements brought about by dislocations and the abundance of carbon atoms in the austenite phase.